Characterization of intermittent structures in the solar wind - Nakwacki, M.S. (2013)
The solar wind (SW) is a suitable natural scenario to study the intermittent nature of magnetohydrodynamic (MHD) turbulence for systems with low dissipation rate. In particular, nonlinear wave-wave interactions can be characterized by the degree of phase correlation and by departures from Gaussianity of the magnetic field. In this work, we study in situ observations of magnetic field intensity from the spacecraft ACE, which is located near one astronomical unit from the Sun, in the SW near Earth. We compute the phase coherence index analyzing two sets of observations, each one consisting of approximately three months during 2008 and 2012, respectively. From these sets of data we characterize intermittent features of the magnetic field intensity corresponding to a solar maximum and a solar minimum. © 2013 International Astronomical Union.